2020
DOI: 10.11144/javeriana.cc21.vrio
|View full text |Cite
|
Sign up to set email alerts
|

Value Relevance of net income, other comprehensive income, and comprehensive income in Brazil

Abstract: This paper uses the Ohlson Model to analyze whether Net Income (NI), Other Comprehensive Income (OCI), and Comprehensive Income (CI) are value relevant for market value and the return of shares of publicy-traded Brazilian companies. To maximize the robustness of the results, we inserted the following control variables for each model: equity per Share (EqPS), Size (S), Industry (I), EBITDA per Share (EbPS), Revenue per Share (RePS), Liquidity (L), and Gross Domestic Product Growth (GDPG). The control variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Meichyel & Dewi (2019) show that NI has a positive influence on stock returns; CI, OCI, and high subjectivity OCI have a negative influence on stock returns, and low subjectivity OCI has no effect on stock returns. Bortoli et al (2020) found NI, OCI, and CI to be relevant values for the market value and stock returns of Brazilian public companies. However, only NI and CI contribute positively in explaining company value.…”
Section: Relevance and Components Of Oci To Stock Market Returns In T...mentioning
confidence: 93%
“…Meichyel & Dewi (2019) show that NI has a positive influence on stock returns; CI, OCI, and high subjectivity OCI have a negative influence on stock returns, and low subjectivity OCI has no effect on stock returns. Bortoli et al (2020) found NI, OCI, and CI to be relevant values for the market value and stock returns of Brazilian public companies. However, only NI and CI contribute positively in explaining company value.…”
Section: Relevance and Components Of Oci To Stock Market Returns In T...mentioning
confidence: 93%
“…En este contexto, surge la pregunta: ¿qué tan útil es conocer cuándo el nivel de ventas es menor al de compras en varios periodos mensuales? Según Bortoli et al (2020), esta interrogante constituye una alerta roja novedosa, ya que los valores de ventas observados por el mercado pueden ser utilizados para predecir y confirmar lo que se esperaba.…”
Section: Introductionunclassified